2023
DOI: 10.3390/s23146414
|View full text |Cite
|
Sign up to set email alerts
|

RSI-YOLO: Object Detection Method for Remote Sensing Images Based on Improved YOLO

Abstract: With the continuous development of deep learning technology, object detection has received extensive attention across various computer fields as a fundamental task of computational vision. Effective detection of objects in remote sensing images is a key challenge, owing to their small size and low resolution. In this study, a remote sensing image detection (RSI-YOLO) approach based on the YOLOv5 target detection algorithm is proposed, which has been proven to be one of the most representative and effective alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The approach is analyzed in comparison to six OOD methods, i.e., RetinaNet-O [30], Faster R-CNN [43], S 2 ANet [31], RoI Transformer [14], AOPG [67], and Oriented R-CNN [15], on both RSI datasets. Furthermore, comparisons are made with nine other OOD methods, such as DRN [33], LO-Det-GGHL [75], CenterMap-Net [47], DPGN [51], Oriented RepPoints [5], YOLOv2-O [28], Rep-YOLO [79], RSI-YOLOv5 [80], and YOLOv8-O [81] on the DOTA dataset. The assessment is broadened with an additional four OOD methods, including Double-Heads [40], Gliding Vertex [68], QPDet [53], and DODet [66] on DIOR-R. As shown in Table 3, the DOTA dataset includes 15 different object categories, denoted as PL, BD, BR, GTF, SV, LV, SH, TC, BC, ST, SBF, RA, HA, SP, and HC.…”
Section: Comparison With the Sota Methodsmentioning
confidence: 99%
“…The approach is analyzed in comparison to six OOD methods, i.e., RetinaNet-O [30], Faster R-CNN [43], S 2 ANet [31], RoI Transformer [14], AOPG [67], and Oriented R-CNN [15], on both RSI datasets. Furthermore, comparisons are made with nine other OOD methods, such as DRN [33], LO-Det-GGHL [75], CenterMap-Net [47], DPGN [51], Oriented RepPoints [5], YOLOv2-O [28], Rep-YOLO [79], RSI-YOLOv5 [80], and YOLOv8-O [81] on the DOTA dataset. The assessment is broadened with an additional four OOD methods, including Double-Heads [40], Gliding Vertex [68], QPDet [53], and DODet [66] on DIOR-R. As shown in Table 3, the DOTA dataset includes 15 different object categories, denoted as PL, BD, BR, GTF, SV, LV, SH, TC, BC, ST, SBF, RA, HA, SP, and HC.…”
Section: Comparison With the Sota Methodsmentioning
confidence: 99%
“…It has been proved that convolutional neural networks have satisfied result on crater detection based on DEM and CCD remote sensing data. For example, the FasterRCNN [21] has already been applied in object detection with higher efficiency compared with previous work,MSA-YOLO [22] is desgined to object detection in DIOR dataset, RSI-YOLOv5 [23] is applied in remote sensing dataset such as DOTA and NWPU-VHR with outperform results, and a Graph Neural Network (GNN) [24] is desgined to execute the semantic segmentation in satellite image data. It can be concluded that deep learning method has great potential in remote sensing data processing.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al [7] present the YOLOv7 model to appeal to the object detection fields. Li et al proposed RSI-YOLO (an improved YOLO) for remote sensing [8]. They added the CBAM attention mechanism to the original model.…”
Section: Related Workmentioning
confidence: 99%